1997
DOI: 10.1097/00003246-199707000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged controlled mechanical ventilation on diaphragmatic function in healthy adult baboons

Abstract: Eleven days of mechanical ventilation and neuromuscular blockade in healthy baboons resulted in nonsignificant changes in hemodynamics, oxygenation, and/or lung function. However, significant impairment in diaphragmatic endurance and strength were seen. Based on these results, it is likely that prolonged mechanical ventilation by itself impairs diaphragmatic function independent of underlying lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 15 publications
7
115
0
7
Order By: Relevance
“…This original account was quickly supported by another study depicting the influence of prolonged MV on in vivo diaphragm function in healthy baboons (6). This primate study concluded that prolonged MV results in significant impairment of diaphragmatic contractile performance as indicated by a decrease in both maximal transdiaphragmatic pressure and diaphragmatic endurance (6). Following these early investigations, scientific interest in the effects of MV on diaphragm structure and function grew rapidly, and numerous animal studies published in 2002-2003 consistently concluded that prolonged MV results in the rapid development of both diaphragmatic atrophy and contractile dysfunction (16,19,33,91,93,98,100).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewmentioning
confidence: 87%
See 2 more Smart Citations
“…This original account was quickly supported by another study depicting the influence of prolonged MV on in vivo diaphragm function in healthy baboons (6). This primate study concluded that prolonged MV results in significant impairment of diaphragmatic contractile performance as indicated by a decrease in both maximal transdiaphragmatic pressure and diaphragmatic endurance (6). Following these early investigations, scientific interest in the effects of MV on diaphragm structure and function grew rapidly, and numerous animal studies published in 2002-2003 consistently concluded that prolonged MV results in the rapid development of both diaphragmatic atrophy and contractile dysfunction (16,19,33,91,93,98,100).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewmentioning
confidence: 87%
“…This landmark research revealed that 48 h of controlled MV (i.e., full ventilator support of breathing) resulted in significant loss of diaphragm mass and a large reduction in maximal diaphragmatic specific force production. This original account was quickly supported by another study depicting the influence of prolonged MV on in vivo diaphragm function in healthy baboons (6). This primate study concluded that prolonged MV results in significant impairment of diaphragmatic contractile performance as indicated by a decrease in both maximal transdiaphragmatic pressure and diaphragmatic endurance (6).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewmentioning
confidence: 94%
See 1 more Smart Citation
“…is characterized by a reduction in diaphragm force generation capacity due to controlled mechanical ventilation (CMV) and was recently shown to occur in humans 1 , being well-recognized in animal models as well, like rats 2,3 , rabbits 4 , piglets 5 , and baboons 6 .…”
Section: Ventilator-induced Diaphragmatic Dysfunction (Vidd)mentioning
confidence: 99%
“…Animals did not receive anesthetic doses in a continuous form or neuromuscular blockers, like in other studies 6,10 . Barbiturates and neuromuscular blockers have deleterious effects in skeletal muscle function 29 .…”
Section: Analysis Of Experimental Designmentioning
confidence: 99%